O olhar como experiência: a pintura - Rela, Maryana Lemos Nogueira [UNESP] (2015)
This research is constituted by two complimentary parts: the first one reports the creative process of the paintings produced by myself between 2013 and 2015, which are exhibited here. The key-concepts analyzed on the following chapters are originated from the report and aim to expose reflections derived from practice by establishing links with other authors and artists. The dissertation focuses on the act of seeing, since the paintings I produce require direct observation of visual references. In that sense, the act of looking at things around me led to the finding that I'm not visible to myself, and starting from this premise, the research investigates the necessity of visual perception of oneself, by analyzing self-portrait paintings and the usage of instruments that make us visible, such as the mirror and photograph, and the visual perception of others, by examining our relation with the objects that belong to the interior of a home. It is also presented an investigation of two artists: Jean-Baptiste Siméon Chardin and Giorgio Morandi. The research conclusions, in accordance with Silvio Zamboni conceptions, are contained in the produced paintings.